Tathwiiru Wasaa`Ithi Lu'batid Domiino Litarqiyatil Mufradaatil Lughah Al-'Arabiyyah Wa Mahaaratil Kalaam Fi Al-Madrasah Ad-Diniyyah At-Ta'limiyyah Zainul Hasan Genggong. - Rachmawati, Devi Aprilia; Muhammad Sugianto; Ainur Rofiq Sofa (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2025)
This study aims to develop instructional media in the form of a domino card game to enhance vocabulary mastery and speaking skills on the topic of al-hayawan for second-grade students at Madrasah Diniyah Ta’limiyah Zainul Hasan Genggong. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media was validated by material and media experts, resulting in an average score of 97.7% for content feasibility and 96.3% for media design, both categorized as